Museum Pedagogy in The Construction of Fiqh Watan: Curatorial Principles, Historical Representation and Islamic Epistemology in Pahang, Malaysia - Jalal, Ahmad Farid Abd; Rahim, Rahimin Affandi Abdul; Alias, Ahnaf Wafi; Yusof, Azman; Rahman, Mohammad Taufiq (Program Studi Studi Agama-Agama Pascasarjana UIN Sunan Gunung Djati Bandung, 2026)
This article examines the role of museums as a strategic pedagogical medium in the construction and understanding of fiqh watan, with a case study focused on the state of Pahang. Departing from conventional approaches to fiqh education that are predominantly textual and ahistorical, the study argues that fiqh should be understood as a living law rooted in local history, customs, institutions, and collective memory. Grounded in an Islamic epistemological framework based on tawḥīd and adab, the article conceptualizes the museum as an epistemological institution that constructs historical meaning and legal authority through curatorial selection and interpretation of artefacts. Employing a qualitative approach grounded in conceptual and interpretive analysis, this study integrates literature from museum studies, Islamic education, and local legal history. The findings demonstrate that museum-based pedagogy grounded in fiqh watan enables a holistic integration of farḍ ‘ayn and farḍ kifāyah through artefact-centered engagement. The article further proposes three curatorial principles derived from Islamic epistemology, i.e. object uniqueness, high quality (itqān), and historical representativeness as epistemic criteria for the development of Islamic museums. From a decolonial perspective, the study challenges the claim of neutrality in modern museums and proposes fiqh watan-based museums as counter-archives that restore epistemic authority to local historical experience. Overall, this article contributes to the discourse in Islamic education, heritage studies, and museum studies by positioning the museum as an institution of tarbiyah that integrates law, history, and local identity.